Treatment of Cytokine Storm in COVID-19 Patients With Immunomodulatory Therapy. Issue 10 (November 2020) - Yessayan, Lenar; Szamosfalvi, Balazs; Napolitano, Lena; Singer, Benjamin; Kurabayashi, Katsuo; Song, Yujing; Westover, Angela; Humes, H. David
Abstract : Observational evidence suggests that excessive inflammation with cytokine storm may play a critical role in development of acute respiratory distress syndrome (ARDS) in COVID-19. We report the emergency use of immunomodulatory therapy utilizing an extracorporeal selective cytopheretic device (SCD) in two patients with elevated serum interleukin (IL)-6 levels and refractory COVID-19 ARDS requiring extracorporeal membrane oxygenation (ECMO). The two patients were selected based on clinical criteria and elevated levels of IL-6 (>100 pg/ml) as a biomarker of inflammation. Once identified, emergency/expanded use permission for SCD treatment was obtained and patient consented. Six COVID-19 patients (four on ECMO) with severe ARDS were also screened with IL-6 levels less than 100 pg/ml and were not treated with SCD. The two enrolled patients' PaO2 /FiO2 ratios increased from 55 and 58 to 200 and 192 at 52 and 50 hours, respectively. Inflammatory indices also declined with IL-6 falling from 231 and 598 pg/ml to 3.32 and 116 pg/ml, respectively. IL-6/IL-10 ratios also decreased from 11.8 and 18 to 0.7 and 0.62, respectively. The two patients were successfully weaned off ECMO after 17 and 16 days of SCD therapy, respectively. The results observed with SCD therapy on these two critically ill COVID-19 patients with severe ARDS and elevated IL-6 is encouraging. A multicenter clinical trial is underway with an FDA-approved investigational device exemption to evaluate the potential of SCD therapy to effectively treat COVID-19 intensive care unit patients.